Exploring structure and dynamics of the polylactic‐co‐glycolic acid–polyethylene glycol copolymer and its homopolymer constituents in various solvents using all‐atom molecular dynamics. Issue 31 (14th June 2022) - Nyambura, Chris W.; Sampath, Janani; Nance, Elizabeth; Pfaendtner, Jim
Abstract: Polylactic‐co‐glycolic acid (PLGA)‐basedpolymers are synthetic materials that are prominent in drug delivery. PLGA homopolymer is biodegradable, biocompatible and is often polymerized to polyethylene glycol (PEG) to form a block copolymer used to form core‐shell nanoparticles. PEG is known for reducing blood clearance and opsonization, in addition to imparting "stealth" properties to various drugs and biomaterials. Current formulation methodologies for PLGA–PEG copolymer nanoparticles can be tuned to control key parameters for improved therapeutic delivery; however, molecular‐level understanding of copolymer‐solvent interactions during nanoparticle formulation is lacking. Therefore, three different PLGA–PEG/solvent pairs are examined, in comparison to their homopolymer constituents, to better understand copolymerization effects and its impact on nanoparticle formulation. Results show that at room temperature PLGA–PEG oligomers in dimethyl sulfoxide are the most rigid in good solvent conditions (Flory exponent >0.5) and have the largest end‐to‐end relaxation times when compared to acetone and water. PEG has a Flory exponent of ~0.5 in both water and acetone, showing that the molecular dynamic model that is employed can reproduce its amphiphilic nature in solution. Knowledge of PLGA–PEG structure and dynamics can be used in the design of novel biomedical technologies that improve drug efficacy and reduce cost of treatment. Abstract : Structure and dynamics of the polylactic‐co‐glycolic acid–polyethylene glycol (PLGA–PEG) diblock copolymer were explored in three different solvents, ubiquitous in the formation of PLGA–PEG core‐shell nanoparticles.